Hyperbilirubinemia predicts the infectious complications after esophagectomy for esophageal cancer - Muneoka, Yusuke (Ann Med Surg (Lond), 2019)
BACKGROUND: Surgical stress and inflammation can cause hyperbilirubinemia, which sometimes occurs after esophagectomy for esophageal cancer (EC). The aim of this study was to elucidate the clinical significance of postoperative hyperbilirubinemia in the management of EC patients. MATERIALS AND METHODS: We retrospectively reviewed records of 81 EC patients who underwent esophagectomy from 2009 to 2014. We compared the clinicopathological and perioperative factors, including the presence of hyperbilirubinemia (total bilirubin ≥1.5 mg/dL), between patients with postoperative infectious complications (PIC group) and those without (Non-PIC group). RESULTS: PIC developed in 52 patients (64.2%). There were significant differences in incidence of postoperative hyperbilirubinemia between the PIC group and the non-PIC group (34.6% vs. 3.4%, P = 0.002), as well as the approach of esophagectomy (P = 0.045), the surgical duration (469 vs. 389 min, P < 0.001), the amount of blood loss (420 vs. 300 mL, P = 0.018), the frequency of intraoperative blood transfusions (32.7% vs. 6.9%, P = 0.012) and the peak postoperative C-reactive protein level (17.3 vs. 8.6 mg/dL, P = 0.007). Multivariate analysis revealed hyperbilirubinemia was independently associated with the occurrence of PICs (odds ratio: 38.6, P = 0.010). The median time to the diagnosis of hyperbilirubinemia was significantly shorter than that of PICs (3.0 vs. 4.5 days, P = 0.025). CONCLUSIONS: Postoperative hyperbilirubinemia was associated with the occurrence of PICs and frequently occurred before any PICs become apparent. More attention should be paid to the serum bilirubin level in the management after esophagectomy for EC.